Reverse Vaccinology and Immunoinformatic Assisted Designing of a Multi-Epitopes Based Vaccine Against Nosocomial Burkholderia cepacia - Alsowayeh, Noorah; Albutti, Aqel; Al-Shouli, Samia T. (Frontiers in Microbiology, 2022)
In order to handle or reduce the burden of antibiotic resistant (AR) infections, different measures can be taken, such as reducing use of antibiotics while treatment human and animal illnesses, in agriculture, and limit its dispose to the environment. Pseudomonas cepacia is a Gram-negative nosocomial pathogen and is considered as a troublesome pathogen. There is no licensed vaccine available against the pathogen, which is is resistant to several classes of antibiotics. In order to identify protective antigens screened from pathogen genomes, substantial efforts are put forth to identify antigens that can be easily evaluated experimentally. P. cepacia completely sequenced genomes has a total of 28966 core proteins. Further, 25,282 proteins were found redundant while 3684 were not. Subcellular localization revealed that 18 were located extracellularly, 31 in the outer membrane, 75 in the periplasm, and 23 were virulent proteins. All seven proteins (Flagellar hook protein (FlgE), Fimbrial biogenesis outer membrane usher protein, Type IV pilus secretin (PilQ), Cytochrome c4, Flagellar hook basal body complex protein (FliE)) were tested for antigenicity, toxicity, and solubility during predication of B-cell derived T-cell epitopes. A vaccine construct consisting of 14 selected epitopes and adjuvant cholera toxin B subunit (CTBS) was constructed using GPGPG linkers. To test whether the constructs interact with MHC-I, MHC-II, and Toll-like receptor 4 (TLR4) immune receptors, molecular docking was performed and further analyzed in molecular dynamics simulations that affirms strong intermolecular binding and stable dynamics. Additionally, complexes binding free energies were determined that concluded robust interaction energies dominated by van der Waals. In summary, the designed vaccine showed promising protective immunity against P. cepacian and needs to be examined in experiments.